QUALITY FUNCTION DEPLOYMENT (QFD) APPLIED TO THE VARIABLES THAT INFLUENCE QUALITY COSTS IN MECHANIZED FOREST HARVEST OPERATIONS - Silva Oliveira, Gustavo; Casemiro Soares, Philipe Ricardo; Sampietro, Jean Alberto (Floresta, 2020)
Globalization and client demands result in the need for investments for the survival of the companies. Forest harvest represents the highest costs and losses of wood production. Quality function deployment (QFD) is recommended to achieve quality by detecting customer needs. Thus, this study aimed to determine the variables that influence quality costs in the mechanized harvest to reach the quality control of forest activity. The research was developed in a company located in the State of Santa Catarina, Brazil. The variables that influence quality costs in four categories (evaluation, prevention, internal and external flaws) were identified. The QFD method was used to translate the needs of internal and external customers (critical success factors) of mechanized harvesting activities into measurable technical characteristics (variables that influence quality costs), determining the weight for each relationship and, consequently, the balance of the categories, besides the correlations of the variables evaluated as strong, medium, weak, and non-existent. Among the 29 variables identified, 18 consisted of evaluation and prevention, representing the relative weights of 37.17% and 26.49%, respectively, and 11 represented internal and external flaws, with values of 26.57% and 9.73%, respectively. The correlation matrix found 334 correlation of the 406 cells: 195 (58%) strong, 86 (26%) medium, and 53 (16%) weak. In conclusion, the company must improve process quality by investing in evaluation and prevention aimed at reducing non-conformities and expansion of revenues.